Factors associated with the platelet count in patients with chronic hepatitis C. Issue 5 (May 2015) - Tana, Michele M.; Zhao, Xiongce; Bradshaw, Alyson; Moon, Mi Sun; Page, Sandy; Turner, Tiffany; Rivera, Elenita; Kleiner, David E.; Heller, Theo
Abstract: Background: There are many potential causes of thrombocytopenia in patients with chronic hepatitis C (CHC). Aims: We sought to determine the association between thrombopoietin (TPO) level, immature platelet fraction (IPF), immunoglobulin G (IgG) level, spleen size, and the platelet count in CHC. Methods: We studied a consecutive sample of patients enrolled in an observational study at a referral-based research center, excluding subjects based on eligibility criteria. TPO, glycocalicin, and von Willebrand Factor (vWF) levels were determined using stored sera. Hepatic fibrosis was assessed via transient elastography (TE) when available, and clinical laboratory values and radiologic data were obtained from the medical record. We performed analyses of the relationships between independent variables and the platelet count. Results: On univariate analysis, the following variables were significantly associated with the platelet count: age, alanine aminotransferase (ALT), direct bilirubin, total bilirubin, IPF, international normalized ratio (INR), spleen size, vWF, glycocalicin, fibrosis stage on liver biopsy, and TE (P-values all < 0.05). A multivariable model determined that imputed TE score, TPO, IPF, and spleen size were independently associated with the platelet count (P-values all < 0.05). Conclusions: The platelet count in CHC is significantly associated with fibrosis, TPO level, IPF, and spleen size. Our findings challenge the proposed mechanism of decreased TPO levels or decreased bone marrow production of platelets as a cause of thrombocytopenia in CHC. Future studies focusing on the effects of fibrosis and splenomegaly on platelets may shed more light on the pathophysiology of thrombocytopenia in patients with CHC. Highlights: Stored sera was tested for thrombopoietin, glycocalicin, and von Willebrand Factor. Immature platelet fraction correlated with platelet count on univariate analysis. Spleen size correlated with platelet count on univariate analysis. Fibrosis, TPO, IPF, and spleen size are associated with the platelet count.